Meaningful Work dan Eudaimonic Workplace Well-Being pada Guru SMA - Asiva, Vionanda; Rahmi, Tuti (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This study aims to examine the relationships between Meaningful Work and Eudaimonic Workplace Well-being among teachers in a district in West Sumatra. Meaningful Work was measured using the Work and Meaning Inventory (WAMI), while Eudaimonic Workplace Well-being was measured using the Eudaimonic Workplace Well-being Scale (EWWS). The research employeed a correlational quantitative design involving all teachers through a total sampling technique. Data were analyzed using Spearman’s Rho to test the correlation between variabels. The result showed a strong and significant positive correlation between Meaningful Work and Eudaimonic Workplace Well-being (r = 0,650; p = 0,000). This indicates that the higher the teachers’ Meaningful Work, the higher their Eudaimonic Workplace Well-being.